Bibliometric analysis of ferroptosis: a comprehensive evaluation of its contribution to cancer immunity and immunotherapy - Wang, Zhen; Zhang, Hui; Wang, Li; Ma, Zhen; Cui, Yu’ang; Fu, Haitian; Yu, Chunjing (Frontiers in Oncology, 2023)
Background: In the past 5 years, ferroptosis-associated cancer immunity has been attracted significant research interest. Objective: This study was performed to identify and analyze the global output trend for ferroptosis in cancer immunity. Methods: Relevant studies were retrieved from the Web of Science Core Collection on Feb 10th, 2023. The VOSviewer and Histcite softwares were utilized to perform the visual bibliometric and deep mining analyses. Results: A total of 694 studies (530 articles (76.4%) and 164 (23.6%) review articles) were retrieved from the Web of Science Core Collection for visualization analyses. The top 3 key keywords were ferroptosis, prognosis and immunotherapy. The top 30 local citation score (LCS) authors were all collaborators of Zou Weiping. Deep mining of 51 nanoparticle-related articles showed that BIOMATERIALS was the most popular journal. The primary goal of gene signatures related to ferroptosis and cancer immunity was to establish prognostic predictions. Conclusion: There has been a significant increase in ferroptosis-associated immune publications in the recent 3 years. The key research hotspots include mechanisms, prediction and therapeutic outcomes. The most influential article was from the Zou Weiping’s group, which proposed that system xc-mediated ferroptosis is induced by CD8(+) T cell-secreted IFNγ after PD-L1 blockage for immunotherapy. The frontier of research in the field of ferroptosis-associated immune is the study on nanoparticle and gene signature The limitation of this bibliometric study is that publications on this topic are few. The graphic abstract is shown in Fig 9.